2011
DOI: 10.1017/s0022029911000045
|View full text |Cite
|
Sign up to set email alerts
|

Milk fatty acid characterization and genetic parameter estimates for milk conjugated linoleic acid in buffaloes

Abstract: The objectives of this study were to analyse buffalo milk fat composition, to verify the activity of Delta (9)-desaturase enzyme in the mammary gland, as well as to estimate additive genetic variances for milk, fat and protein yield, and milk cis-9,trans-11 conjugated linoleic acid percentage (cis-9,trans-11 CLA%). A total of 3929 lactation milk yields (MY) records from 2130 buffaloes and 1598 lactation fat (FY) and protein (PY) yield records from 914 buffaloes were analysed. For cis-9,trans-11 CLA% percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…These factors may also influence the fatty acid composition of buffalo milk (Secchiari et al, 2004;Varricchio et al, 2007). Indeed, our results only partially agreed with previous data on water buffalo (e.g., Tonhati et al, 2011;Zotos and Bampidis, 2014). Additionally, other studies were also often performed on a lower number of animals and different rearing conditions (e.g., Menard et al, 2010).…”
Section: Detailed Milk Fatty Acid Profile Of Buffalo Milksupporting
confidence: 85%
See 2 more Smart Citations
“…These factors may also influence the fatty acid composition of buffalo milk (Secchiari et al, 2004;Varricchio et al, 2007). Indeed, our results only partially agreed with previous data on water buffalo (e.g., Tonhati et al, 2011;Zotos and Bampidis, 2014). Additionally, other studies were also often performed on a lower number of animals and different rearing conditions (e.g., Menard et al, 2010).…”
Section: Detailed Milk Fatty Acid Profile Of Buffalo Milksupporting
confidence: 85%
“…Values for milk production in buffaloes of the present study were lower than previous literature data (e.g., Tudisco et al, 2013). Similar MF percentages were described (e.g., Tufarelli et al, 2008;Salari et al, 2013), although sometimes higher values were reported (e.g., Tonhati et al, 2011), likely reflecting the effect of different management, feeding, and environmental conditions. These factors may also influence the fatty acid composition of buffalo milk (Secchiari et al, 2004;Varricchio et al, 2007).…”
Section: Detailed Milk Fatty Acid Profile Of Buffalo Milksupporting
confidence: 73%
See 1 more Smart Citation
“…This deduction was confirmed herein through the activity of the Δ 9 -desaturase enzyme in the mammary gland, which was estimated from four pairs of fatty acids that represent a product/substrate relationship for this enzyme. The current results revealed that the activity of this enzyme takes a part in fatty acid synthesis in the mammary gland of camels, despite the fact that factors affecting Δ 9 -desaturase activity are not yet well explained (Lock and Garnsworthy, 2002; Tonhati et al 2011). In fact, it is evident that the activity of oleic-desaturase and overall-Δ 9 -desaturase were the only indices decreased in stabled camels compared to grazing camels.…”
Section: Discussionmentioning
confidence: 64%
“…Water buffaloes have genetic potential for productive traits (Aspilcueta-Borquis et al 2010a,b,c;Tonhati et al 2011) and also for reproductive ones (Galeazzi et al 2010a,b). Seno et al (2012) demonstrated that the progeny test and selection permit to obtain genetic gain.…”
Section: Introductionmentioning
confidence: 99%